Zakat Distribution for Women the Prostitution Victim as the Concept of Riqab - Alfin, Aidi; Sudarman, Revoranda; Zhilal Haq, Muhammad; Idris, Mashair (Fakultas Syariah Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi, Indonesia, 2023)
There are eight groups of zakat recipients and one of them is the riqab which is interpreted as a slave. The textual meaning of the riqab is no longer relevant today considering that slavery no longer exists. So that is the reason that the asnaf riqab is indirectly removed. This needs to be considered again so that the distribution of zakat can be evenly distributed to the eight asnaf. The current interpretation of the meaning of the riqab can be interpreted as human trafficking which is related to this, namely victims of sexual exploitation or prostitution. So the question is how to interpret the riqab for women who are victims of prostitution. This research is qualitative research in the form of a library research with data collection techniques, collecting and reading literature related to this research. The results of the research show that in this context the riqab is interpreted as a person who is shackled by social and religious beliefs, so that this problem includes women who are victims of prostitution. As the distribution of zakat for asnaf riqab does not give him the right to tamlik zakat assets, but rather to redeem the money for his automatic release to his master. Likewise, it is applied to the meaning of the riqab of prostitution victims, that zakat funds are used for rehabilitation with the aim of providing guidance so that the mustahik can get out of their shackled status.